PENGARUH PENGUNGKAPAN CSR DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN DENGAN KEPEMILIKAN ASING SEBAGAI VARIABEL MODERASI - Sri Kawuri; Riana Sitawati; Sam’ani Sam’ani (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
Financial performance becomes a matter of great concern toan investor but must also take into account the social andenvironmental responsibilities of the company. This study aims toanalyze the effect of CSR disclosure and environmental performanceon financial performance with moderation of foreign ownership.Respondents of this research are manufacturing companies listed onthe BEI 2011 - 2015 and registered in PROPER in 2011 - 2015. Thenumber of samples of 85 companies is taken based on PurposiveSampling technique. Data collection using documentation method.The data analysis to test the hypothesis using multiple regression iscompleted with SPSS program.From the results of this study obtained the conclusion that:Disclosure of CSR has a significant positive effect on financialperformance, environmental performance has no effect on financialperformance. In addition, this research finds that foreign ownershipmoderates the effect of CSR disclosure on financial performance withnegative direction and can not moderate the influence ofenvironmental performance on financial performance.